Patients with chronic lymphocytic leukemia and complex karyotype show an adverse outcome even in absence of TP53/ATM FISH deletions - Puiggros, Anna (Oncotarget, 2017)
Genomic complexity identified by chromosome banding analysis (CBA) predicts a worse clinical outcome in CLL patients treated either with standard or new treatments. Herein, we analyzed the clinical impact of complex karyotypes (CK) with or without high-risk FISH deletions (ATM and/or TP53, HR-FISH) in a cohort of 1045 untreated MBL/CLL patients. In all, 99/1045 (9.5%) patients displayed a CK. Despite ATM and TP53 deletions were more common in CK (25% vs 7%; P < 0.001; 40% vs 5%; P < 0.001, respectively), only 44% (40/90) patients with TP53 deletions showed a CK. CK group showed a significant higher two-year cumulative incidence of treatment (48% vs 20%; P < 0.001), as well as a shorter overall survival (OS) (79 mo vs not reached; P < 0.001). When patients were categorized regarding CK and HR-FISH, those with both characteristics showed the worst median OS (52 mo) being clearly distinct from those non-CK and non-HR-FISH (median not reached), but no significant differences were detected between cases with only CK or HR-FISH. Both CK and TP53 deletion remained statistically significant in the multivariate analysis for OS. In conclusion, CK group is globally associated with advanced disease and poor prognostic markers. Further investigation in larger cohorts with CK lacking HR-FISH is needed to elucidate which mechanisms underlie the poor outcome of this subgroup.